The Effect of Good Government Governance on the Financial Reports Quality: The Case of Provincial Capital Governments in Indonesia - Masnila, Nelly; Mayasari, Riana; Firmansyah, Firmansyah; Febriantoko, Jovan; Said, Jamaliah (International Journal of Business, Management and Economics, 2021)
This study aimed to determine the relationship and effect of the GGG variable on the quality of the financial reports in municipal governments in Indonesia by implementing the IIAG (The Ibrahim Index of African Governance) indicator. The variables of this study consist of the participant, legal culture, transparency, responsiveness, public interest orientation, fairness, effectiveness and efficiency, accountability, strategic vision, and human development as independent variables and the quality of financial reports as dependent variables. The method in this study was quantitative, so it was found that partially, only responsive and accountability variables significantly affected the quality of the financial reports. Meanwhile, other independent variables such as participants, legal culture, transparency, public interest orientation, fairness, effectiveness and efficiency, strategic vision, and human development had no significant effect on the quality of financial reports. However, simultaneously, all independent variables had a significant effect on the quality of financial reports. The level of the coefficient of determination obtained was equal to Adj. R2 = 0.299. It means that the quality of local government financial reports was influenced by the independent variable by 29.9%, while 70.1%was influenced by other variables not examined in this study